2017
DOI: 10.1063/1.4984913
|View full text |Cite
|
Sign up to set email alerts
|

Particle dynamics in wall-bounded thermal counterflow of superfluid helium

Abstract: The motions of relatively small particles in wall-bounded thermal counterflow of superfluid helium are experimentally investigated, above 1 K, by using the particle tracking velocimetry technique. The effect of a solid boundary on this quantum flow has received little attention to date, and the focus here is on the corresponding flow-induced particle dynamics. The velocity and velocity difference statistical distributions of the particles are computed at length scales straddling two orders of magnitude across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The counterflow velocity U ns = U n −U s creates a random vortex tangle with an energy spectrum, peaking at the intervortex scale ℓ and with a close to Gaussian statistics, as demonstrated experimentally in Refs. [14][15][16] and rationalized theoretically in Refs. 18,33 .…”
Section: Qualitative Analysis Of Anisotropic Counterflow Turbulencementioning
confidence: 92%
See 2 more Smart Citations
“…The counterflow velocity U ns = U n −U s creates a random vortex tangle with an energy spectrum, peaking at the intervortex scale ℓ and with a close to Gaussian statistics, as demonstrated experimentally in Refs. [14][15][16] and rationalized theoretically in Refs. 18,33 .…”
Section: Qualitative Analysis Of Anisotropic Counterflow Turbulencementioning
confidence: 92%
“…The function D(k, θ) in Eqs. (16) describes the level of decorrelation of the normal-fluid and superfluid velocity components by the counterflow velocity. Within the approximation (16b), D(k, θ) defines the rate of energy dissipation caused by mutual friction:…”
Section: Physical Origin Of the Strong Anisotropy Of Counterflow Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies 15,16 measured the statistics of the superfluid component. Recent theoretical analysis 17 found that the energy spectra in counterflow turbulence are not scale-invariant and cannot be rigorously connected with apparent scaling exponents of the second-order velocity structure functions measured in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The statistics of turbulent fluctuations was inaccessible. Only few years ago, with the development of breakthrough experimental visualization techniques, the studies of the turbulent statistics of the normal [17][18][19] and superfluid 20,21 components in the 4 He counterflow become possible.…”
Section: Introductionmentioning
confidence: 99%